2021
DOI: 10.1002/ppul.25537
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19: Impact, experiences, and support needs of children and young adults with cystic fibrosis and parents

Abstract: Background: Little is known about the impact of COVID-19 and the United Kingdom's (UK) national shielding advice on people with cystic fibrosis (CF) and their families. This study explored the experiences and support needs of children and young adults (CYAs) with CF, and parents who have a child with CF, during the COVID-19 pandemic. Methods: CYAs with CF and parents of CYAs with CF completed a UK wide online survey with open and closed questions exploring experiences, information and support needs and decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 31 publications
1
20
0
2
Order By: Relevance
“…Parents were concerned about their child's social and emotional development. Studies from several countries including Turkey and the United Kingdom (UK), showed similar findings with increased levels of anxiety, stress, and depression among children with CF and their families [17,18]. During the early COVID-19 restrictions period (March-April 2020), an Irish study of 1,000 people found that 41% felt lonely, 23% faced depression and 20% reported clinically significant anxiety [19].…”
Section: Discussionmentioning
confidence: 93%
“…Parents were concerned about their child's social and emotional development. Studies from several countries including Turkey and the United Kingdom (UK), showed similar findings with increased levels of anxiety, stress, and depression among children with CF and their families [17,18]. During the early COVID-19 restrictions period (March-April 2020), an Irish study of 1,000 people found that 41% felt lonely, 23% faced depression and 20% reported clinically significant anxiety [19].…”
Section: Discussionmentioning
confidence: 93%
“…This concern was heightened since the outbreak of COVID-19, as study participants had to deal with the widespread public fear of cough, a common symptom of CF and COVID-19, and the inappropriate reactions of some people. Collaco and colleagues (2021), based on a qualitative study, found that most parents, children, and adolescents are worried about the COVID-19 and their health ( Collaço et al, 2021 ). Although spreading the virus is a major concern in CF patients, these patients faced other challenges in the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic and lockdown experience have significantly disrupted the lives of adolescent patients with CF and their parents. It has had subsequent negative effects on their psychological health ( Collaço et al, 2021 ). This outbreak has had global impacts on social life, economy, and health care.…”
Section: Introductionmentioning
confidence: 99%
“…According to Collaço et al, over 75% of studied CF patients worried about how possible COVID-19 infection might influence their health [ 38 ]. In the German study about COVID-19-related fears, people with CF assessed the risks of the pandemic, severe course of the disease and the possibility of death due to COVID-19 infection as being more serious than they were for than healthy people [ 39 ].…”
Section: Discussionmentioning
confidence: 99%